2023
DOI: 10.3390/en16237749
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Deposition of Pollutants on the Surface of Photovoltaic Modules

Janusz Teneta,
Mirosław Janowski,
Karolina Bender

Abstract: This article presents the results of an experiment to measure the mass of contaminants naturally deposited on the surface of photovoltaic modules. Six types of PV modules included in the installation located on the roof of the C3 building (AGH campus, Krakow, Poland) were tested. More than 120 contamination samples were collected during the experiment, which lasted from 23 March to 15 June 2022. Detailed analysis showed a clear relationship between the tilt angle of the photovoltaic modules and the amount of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…In addition, a white backsheet is advantageous for another reason. Research on the deposition of dirt on PV modules operating in urban conditions has shown that on average, 10-11% more dirt settles on modules with a black backsheet than on modules with a white backsheet [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a white backsheet is advantageous for another reason. Research on the deposition of dirt on PV modules operating in urban conditions has shown that on average, 10-11% more dirt settles on modules with a black backsheet than on modules with a white backsheet [16].…”
Section: Introductionmentioning
confidence: 99%